Development of the viscous plane damper applicable in limited space within structures subjected to dynamic loads - Mohd Ali, Mohd Ridzuan; Hejazi, Farzad (Multidisciplinary Digital Publishing Institute, 2024)
Shipping impact and wave loads impose dynamic loads on jetties and platforms in the sea, which cause the vibration of structures. Recently, many advanced viscous damper devices have been developed for implementation in structures to diminish structural vibration due to earthquakes or wind. However, the longitudinal configuration of conventional viscous damper devices requires adequate space to locate the damper device within the frame structure, which limits the application of viscous dampers for use in jetties or platforms to dissipate the vibrations imposed by ship impact or wave force. For this reason, in this study, an attempt has been made to develop a new viscous plane damper device applicable in limited space positions where the longitudinal damper device is not able to fit. For this purpose, the initial design for the viscous plane damper device is proposed, and the prototype of the device is manufactured. Then, the performance of the fabricated viscous plane damper is examined through experimental tests by applying cyclic loads using a dynamic actuator. In order to investigate the effect of the diameter and configuration of the piston’s orifices, five different diameters for the orifices of 1, 2, 5, 8, and 10 mm are included, and three different distribution configurations of the orifices in the piston plate as Configurations A, B, and C are manufactured and tested experimentally. The lab testing is conducted by applying cyclic loads with different frequencies to evaluate the performance of the developed plane damper device under various load velocities. Accordingly, the dynamic performance of the damper device, including the damping force, effective damping and stiffness and the energy dissipation capacity obtained from the hysteresis response (force–displacement result), is investigated. The results of the experimental tests prove the functionality of the developed device to generate the desired damping force and vibration energy dissipation during applied cyclic loads. Therefore, the new plane damper device can be implemented in any structure to dissipate the effect of imposed vibration.